Learning based Communication Technology for Visually Impairments Students in the Digital Age - Mardiana, Siska; Istiyanto, S. Bekti; Annisarizki, Annisarizki; Putra, Ari (Jurnal The Messenger, 2024)
Introduction: The aim to this research to determine and analyze how to learning by access and utilization digital technology for high school visually impaired students (SLBN A) at Bandung City, Indonesia, because only in this school provide computer information technology specialization class, so it is important to have learning communication that is appropriate to the conditions of students who study computer technology without using visuals. Methods: This research used qualitative with case study method, and data collection techniques use observation, interviews, and documentation. The participants consist of visually impaired students and teachers, the school principal, and a representative from the West Java Provincial Education Office. Findings: The research findings, reveal several essential aspects of access computers for visually impaired students, such as familiar with screen readers, the ability to remember and utilize shortcuts, proficient typing skills using all ten fingers, and the use of assistive tools. Digital-based learning involves using computers and smartphones due to the various supporting software applications. All participant have the computer skill use to type word, input data to excel, email and as well as search for materials on the internet and participants reported that smartphone was used to communicate, using conference applications, and searching for information online, and some participants used it to produce creative content. Originality: The novelty is a collaborative learning model based on communication technology for visually impaired students. Communication technology enables this collaboration through digital applications and devices that support communication and interaction between students and teachers, and interaction between students.